Production of high-affinity glycosylated anti-mouse conjugated nanobodies in Pichia pastoris - Orioli, Sofía (2025)
Introduction: Nanobodies (NBs) are small antibody fragments derived fromcamelid heavy-chain antibodies, which represent the minimal functionaldomain capable of antigen recognition and binding. NBs are 10 times smallerthan conventional antibodies, exhibit a compact structure, and have high stability,making them ideal for recombinant production. The eukaryotic unicellularsystem Pichia pastoris provides multiple advantages for protein expression,including the ability to perform several eukaryotic post-translationalmodifications such as glycosylation.Methods: In this work, we engineered a modular plasmid sequence that, throughspecific restriction enzyme cuts and ligations, codes the expression of a secretedanti-mouse kappa chain NB fused with various accessory peptides in P. pastoris.This system enables the incorporation of a plastic binding sequence forimmobilization onto polystyrene surfaces, a histidine tag (Hisx6) forpurification, the horseradish peroxidase (HRP) enzyme for chemiluminescencedetection, or the biotinylatable AviTag sequence for detection using a differentmethod, in multiple combinations.Results: We successfully expressed and purified anti-kappa NBs fused to a Hisx6-tag (κNB) and HRP–Hisx6-tag (κNB–HRP), with subsequent structural andfunctional characterization revealing high affinity and specificity for mouseimmunoglobulins. The κNB–kappa light chain domain complex was modeled,showing a fitted surface interaction of the CDR3 domain. The position of a glycanpresent in κNB CDR3 within the complex was modeled, predicting that glycanaddition would not affect the interaction surface. Accordingly, no functionaldifferences were observed in κNB after deglycosylation, indicating that highmannose glycan addition has not interfered with its binding capability.Glycosylated and deglycosylated κNBs fused to HRP were produced withretained HRP activity and proved to be functional as secondary antibodies.Discussion: Our results show the P. pastoris eukaryotic system’s versatility inproducing NBs and conjugated NBs with or without post-translationalmodifications that may be required for diverse biotechnological applications.